PERAN MANAJEMEN SUMBER DAYA MANUSIA UNTUK PENGUATAN EKONOMI PADA USAHA KEDAI 168 - Azhi Fadlih Saputra; Deninda Maryama F.S; Dwi Epty Hidayati; Santi Pertiwi Hari Sandi (Jurnal Pijar, 2023)
The role of human resources in strengthening the economy by increasing per capita income which aims to build the national economy related to the economic growth indicators of the tavern business 168. Micro, small and medium enterprises (MSMEs) contribute to employment and economic growth by employing a large workforce, enabling MSMEs to reduce action. Human resource management (HR) is the management of labor or employees in organizations and companies. The business of work requires manpower so that the supply of labor requires recruitment, selection, evaluation and wages. Descriptive research method with observation of visitor activity. When charged with internet users, employers can recruit employees via the internet using social media accounts to attract job seekers. Use of the internet is very important to run. There are several options to consider when looking for MSME staff. The 186 tavern business must realize the importance of investing in human resources so that the business they run can continue in line with environmental changes. It is important for MSMEs to take part in knowledge development training in order to be able to compete with other companies. HRM has a significant impact on MSMEs to strengthen the economy